The Impact of Instagram Marketing on Consumer Purchase Intention In The Clothing Industry in Miri, Sarawak. - Sylvester Lawai, Liah; Asmaul Husna, Haris Fadzilah (2023)
The study was carried out to analyze the impact of Instagram marketing on consumer purchase intention in the clothing industry in Miri, Sarawak. The objectives of the study are to identify factors impacting consumers' purchase intention towards the clothing industry. Trustworthiness, E-word of mouth, expertise and attractiveness are the factors that have been identified as impacting consumer purchase intention within the context of Instagram marketing in the Clothing Industry in Miri. A nonprobability sampling method is convenience sampling, which is used in this research to select participants. A number of 384 random respondents from Miri is targeted for the data collection on consumer purchase intention within the context of Instagram marketing in the Clothing Industry. Google Forms was used to create questionnaires and widely distributed on the internet, specifically in Miri. The data collected then be analyzed using IBM SPSS Statistics 27. The Source Credibility Theory (SCT) and Theory of Planned Behaviour (TPB) serve as the underpinning theories for this study. Hence, the findings from this study would be helpful for marketers, advertisers, consumers, social media users and policymakers in improving the understanding of consumer behaviour and their intention to purchase clothing in Miri.